A case of 9p deletion syndrome with Duane retraction syndrome - Sinha, Rahul; Dalal, Shamsher; Raju, Uma; John, Biju M.; Negi, Vandana (Journal of Pediatric Genetics, 2012)
The chromosome 9p deletion syndrome is a rare but specific clinical event. The clinical manifestations include dysmorphic facial features (trigonocephaly, midface hypoplasia, upward slanting palpebral fissures, and a long philtrum) and psychomotor retardation. Here we report a child with chromosome 9p deletion with Duane retraction syndrome, which has never been reported in the literature before.
Keywords: 9p deletion; dysmorphism; chromosome; Duane retraction syndrome